KERJA SAMA INDONESIA DAN VIETNAM UNTUK MENGATASI KASUS ILLEGAL, UNREPORTED, UNREGULATED (IUU) FISHING DI LAUT NATUNA MELALUI REGIONAL PLAN OF ACTION (RPOA) TAHUN 2014 - 2020 - Tasya Milya Salsabila, (2021)
The Natuna Sea with its diversity of marine creatures and its beauty is one of the most sought after seas by other countries, besides the fact that this sea is opposite to many other countries. Due to the diversity of marine creatures in the Natuna Sea, many countries are willing to take illegal actions in this sea, which makes Indonesia faced with cases that are usually faced as a country with the largest archipelagic state in the world, namely cases of Illegal, Unreported, Unregulated (IUU). Fishing. This case makes local Indonesian fishermen feel at a loss by reducing their catch in their own country. One of the seas that is prone to foreign fishermen is the Natuna Sea. With various considerations, which Indonesia feels is necessary with an organization or at least a forum to be able to discuss further, finally Indonesia together with several countries have created a forum or action plan which is called the Regional Plan of Action (RPOA). This RPOA aims to create awareness among the participating countries to respect each other's sovereign territory and carry out responsible fishing. Besides that, cooperation is also needed, Indonesia and Vietnam have gone through various kinds of diplomacy and cooperation. The two countries, which have worked together for almost 70 years, share ambitions about how their fisheries develop. This study aims to find out what kind of cooperation between Indonesia and Vietnam through the RPOA. The author uses 3 frameworks of thought in this research, namely Maritime Security, Illegal Fishing, Security Cooperation. In this study, the author uses a qualitative approach and a descriptive type of research which uses 2 data sources, namely primary data and secondary data. The results of the study state that the cooperation between Indonesia and Vietnam as well as the RPOA in Indonesia has succeeded in reducing cases of Illegal, Unreported, Unregulated (IUU) fishing in Indonesia. Key words: Cooperation, Indonesia, Vietnam, IUU Fishing, Natuna Sea, RPOA